Ly6/uPAR-related protein C4.4A as a marker of solid growth pattern and poor prognosis in lung adenocarcinoma - Jacobsen, Benedikte; Muley, Thomas; Meister, Michael; Dienemann, Hendrik; Christensen, Ib Jarle; Santoni-Rugiu, Eric; Lærum, Ole Didrik; Ploug, Michael (Journal of thoracic oncology, 2013)
Introduction - We have recently shown that the protein C4.4A is induced in early precursor lesions of pulmonary adenocarcinomas and squamous cell carcinomas. In the present study, we aimed at analyzing the impact of C4.4A on the survival of non-small cell lung cancer patients and determining whether its unexpected expression in adenocarcinomas could be attributed to a specific growth type (lepidic, acinar, papillary, micropapillary, solid). - Methods - Sections from the center and periphery of the primary tumor, as well as N2-positive lymph node metastases, were stained by immunohistochemistry for C4.4A and scored semi-quantitatively for intensity and frequency of positive tumor cells. - Results - C4.4A score (intensity × frequency) in the tumor center was a highly significant prognostic factor in adenocarcinomas (n = 88), both in univariate (p = 0.004; hazard ratio [95% confidence interval] = 1.44 [1.12-1.85]) and multivariate statistical analysis (p = 0.0005; hazard ratio = 1.65 [1.24-2.19]), demonstrating decreasing survival with increasing score. In contrast, C4.4A did not provide prognostic information in squamous cell carcinomas (n = 104). Pathological stage was significant in both groups. In the adenocarcinomas, C4.4A expression was clearly associated with, but a stronger prognostic factor than, solid growth. - Conclusions - The present results substantiate the potential value of C4.4A as a prognostic marker in pulmonary adenocarcinomas seen earlier in a smaller, independent patient cohort. Importantly, we also show that C4.4A is a surrogate marker for adenocarcinoma solid growth. Recent data suggest that C4.4A is negatively regulated by the tumor suppressor liver kinase B1, which is inactivated in some adenocarcinomas, providing a possible link to the impact of C4.4A on the survival of these patients.
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 19.03.2021